2018
DOI: 10.1007/s12035-018-0937-8
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Neural Interaction Between Central Dopaminergic and Gut Lesions in Parkinson’s Disease Models

Abstract: The exact mechanism of gut dysfunction in Parkinson's disease and, conversely, the role of gut pathology in brain dopaminergic degeneration are controversial. We investigated the effects of nigral lesions on the colonic neurotransmission, the effect of gut inflammation on the nigrostriatal dopaminergic function, and the possible involvement of the vagus nerve and the local renin-angiotensin system (RAS). Nigrostriatal dopamine depletion was performed by bilateral injection 6-hydroxydopamine, and gut inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 76 publications
2
62
0
Order By: Relevance
“…By contrast, when a more chronic administration regimen was used, we did not observe any change in the alpha-synuclein levels. Such a discrepancy might be explained by the lower levels of colonic proinflammatory cytokines that were found in this model when compared to the acute regimen (Garrido-Gil et al 2018). These observations further reinforce the possible role of proinflammatory cytokines and especially TNF-a and IL1-b in Lysates from colonic samples from day 1 to day 4 were subjected to immunoblot analysis using Syn-1, PGP 9.5 and betaactin antibodies.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…By contrast, when a more chronic administration regimen was used, we did not observe any change in the alpha-synuclein levels. Such a discrepancy might be explained by the lower levels of colonic proinflammatory cytokines that were found in this model when compared to the acute regimen (Garrido-Gil et al 2018). These observations further reinforce the possible role of proinflammatory cytokines and especially TNF-a and IL1-b in Lysates from colonic samples from day 1 to day 4 were subjected to immunoblot analysis using Syn-1, PGP 9.5 and betaactin antibodies.…”
Section: Discussionmentioning
confidence: 76%
“…Such a discrepancy might be explained by the lower levels of colonic pro‐inflammatory cytokines that were found in this model when compared to the acute regimen (Garrido‐Gil et al . ). These observations further reinforce the possible role of pro‐inflammatory cytokines and especially TNF‐α and IL1‐β in the regulation of enteric alpha‐synuclein level.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, brain dopamine also modulates the gut inflammation. Garrido‐Gil et al showed that central dopaminergic depletion increased the level of IL‐1β in colon. These lines of evidence may support the possibility above.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time now, it has been hypothesized that the gut may play a crucial role in the etiology of PD. The intestinal microbiome with a similar amount of bacterial cells as human cells, could be the decisive factor linking the environment and neuronal damage in the central nervous system (CNS) of PD patients [10][11][12]. According to the first theory, alpha-synuclein accumulates in the enteric nervous system and retrogradely extends to the brain stem via the vagus nerve and its nucleus dorsalis [13,14].…”
Section: Introductionmentioning
confidence: 99%